2004
DOI: 10.1111/j.0001-2815.2004.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B27: a registry of constitutive peptide ligands

Abstract: The very strong association of human leukocyte antigen (HLA)-B27 with spondyloarthritis might be related to its peptide-presenting properties. The natural polymorphism of this molecule influences both peptide specificity and disease susceptibility. In this study, we present a comprehensive compilation of known natural ligands of HLA-B27 arising from endogenous proteins of human cells, together with a statistical assessment of residue usage among constitutive peptide repertoires of multiple HLA-B27 subtypes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(161 citation statements)
references
References 52 publications
9
148
4
Order By: Relevance
“…Since peptide-elution studies have shown the HLA-B*2705 B-pocket binds almost exclusively arginine [12,28], variable viruses may thus readily escape immune recognition by any alteration of P2. Interestingly two subtly different mechanisms of binding the P2R have been observed in different crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Since peptide-elution studies have shown the HLA-B*2705 B-pocket binds almost exclusively arginine [12,28], variable viruses may thus readily escape immune recognition by any alteration of P2. Interestingly two subtly different mechanisms of binding the P2R have been observed in different crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…We first looked for evidence of extended versions of peptides identified in either ERAP1-silenced cells or ERAP1-competent cells. As shown in Table 1 (28,(32)(33)(34).…”
Section: Erap1 In Hla-b27 Peptide Presentation 287mentioning
confidence: 99%
“…A statistical analysis was then performed as previously described. 40 Briefly, the frequency of each amino acid residue in a given peptide position was normalized against the mean frequency of that residue among the human proteins (http://www.ebi.ac.uk/integr8/StatsAminoPage.do?org ProteomeId ¼ 25), using the w 2 -test with Yates' correction. Bonferroni correction (P-value  20) was then applied.…”
Section: Matrix Generationmentioning
confidence: 99%